The International Trade of Bangladesh: An Empirical Analysis with Gravity Model - Joki, Hossain Mohammed Hye; Haque, Anamul (Asian Development Policy Review, 2022)
We investigate the foreign trade pattern of Bangladesh using the gravity model of international trade. This work studies 24 years of Bangladesh’s bilateral trade with its 52 major trade partners, from 1995 to 2018. We construct a large panel dataset of 3,168 observations to capture the multilateral resistance terms by accounting for two-way trade flows from each country with the others. We use the PPML fixed effects estimator suggested by Silva and Tenreyro (2006) as the most preferred method for gravity-based analysis. We find mixed results regarding the consistency of Bangladesh’s trade pattern with the gravity model predictions. The results suggest that Bangladesh’s export is positively determined by its income and partner countries’ level of development, but it is relatively less influenced by partner countries income. However, Bangladesh’s level of development is observed to be negatively correlated with both export and import. The distance between the trading countries matters less to Bangladesh, and Bangladesh comparatively tends to trade more with distant countries. The results also suggest that tariffs imposed by partner countries do not affect Bangladesh’s export negatively as Bangladesh receives GSP benefits from its major export market. All the results of the fixed effects regression models are robust, and this paper has significant implications in terms of formulating trade policy for Bangladesh.